Kazakh Emigration and Historical Significance of Memories of Mustafa Shokay. / La emigración kazaja y el significado histórico de los recuerdos de Mustafa Shokay - Zholmakhanova, Akerke B.; Tuyakbaev, Gabit A.; Abdrazakov, Kuandyk; Oralova, Gulzira S.; Serdali, Bekzhigit K. (Utopía y Praxis Latinoamericana)
ABSTRACT The aim of the work is to analyze the Kazakh emigration and the historical significance of the first Kazakh emigrant M. Shokay memories. In work analyzed the positions of the Kazakh intelligentsia of the early 20th century in the national liberation struggle are analyzed. The authors show their own point of view on the genre of memoirs. The ways of forming the Kazakh emigration in the article are considered in relation to the social and political events of the beginning of the 20th century. The article traces how Shokay’s positions in the political struggle are reflected in his memoirs. RESUMEN El objetivo del trabajo es analizar la emigración kazaja y la importancia histórica de los primeros recuerdos del emigrante kazajo, M. Shokay. En el trabajo se analizan las posiciones de la intelligentsia kazaja de principios del siglo XX en la lucha por la liberación nacional. Los autores muestran su propio punto de vista sobre el género de las memorias. Las formas de formar la emigración kazaja en el artículo se consideran en relación con los acontecimientos sociales y políticos de principios del siglo XX. El artículo describe cómo las posiciones de Shokay en la lucha política se reflejan en sus memorias.